MONITORING SEBARAN DAN KERAPATAN MANGROVE MENGGUNAKAN TRANFORMASI NDVI PADA CITRA SENTINEL-2 DI PROVINSI SULAWESI BARAT - Malik, Abdul; Ali, Muhammad Ichsan; Jalil, Abd. Rasyid; Zhiddiq, Sulaiman; Mannan, Abdul; Musyawarah, Rahma (Jurnal Environmental Science, 2024)
The application of the Normalized Difference Vegetation Index (NDVI) on multispectral satellite imagery has been extensively used to assess the quantitative and qualitative aspects of mangrove vegetation. However, the use of Sentinel-2 imagery for this purpose is still relatively new. This research aims to monitor the distribution and density of mangrove vegetation in West Sulawesi by implementing NDVI transformation on Sentinel-2 imagery. The mangrove forest in Mamuju Regency, located in West Sulawesi, is one of the rich areas of mangrove forests on the island of Sulawesi, Indonesia. However, this region also exhibits disturbances in the mangrove ecosystem, resulting in limited monitoring efforts. By utilizing NDVI transformation, we identified the distribution and density of mangrove vegetation using Sentinel-2 imagery. The accuracy of image classification was evaluated using the confusion matrix method, and further analysis was conducted using linear regression to test the relationship between NDVI and mangrove density values obtained from field surveys. The results indicate that the total area of the mangrove forest reaches 1,798 hectares distributed along the coastal areas in the districts of Sampaga, Papalang, Kalukku, Mamuju, Simboro, Tapalang Barat, and Tapalang. Nearly 60% of this area has high mangrove density, while approximately 7% to 9% falls into the low and lowest density categories. NDVI values range from 0.06 to 0.81, with the highest value found in the Mamuju District and the lowest in the Papalang District. The correlation between NDVI and mangrove density shows a strong positive relationship (R=0.78). Therefore, Sentinel-2 imagery demonstrates high accuracy and potential for the development of predictive models for mangrove vegetation density. These findings have significant implications for the development of conservation policies and environmental management, as well as raising public awareness of the importance of preserving mangrove forests.